Pengaruh Fee Audit, Time Budget Pressure, dan Pengalaman Auditor pada Kualitas Audit - Ni Made Candra Primandini; Made Yenni Latrini (Owner : Riset dan Jurnal Akuntansi, 2025)
The quality of audits performed by auditors is a type of assessment of auditor behavior, is shaped by factors originating from within and outside the auditor’s control. This study investigates the impact of audit fees, time budget pressure, and auditor's experience on the quality of audits. This study employs an associative quantitative research methodology to thoroughly investigate the relationship between audit remuneration, temporal constraints, and professional background on the caliber of audit quality. The research carried out at the Public Accounting Firm of Bali Province has been officially registered with the Indonesia Institute of Public Accountants (IAPI) in 2023. The primary focus of this study was on auditors. A purposive sampling strategy was employed to identify a sample of 48 participants for the research. The employed analysis technique is multiple regression analysis. The investigation indicates that audit fees and the auditor's experience enhance the caliber of audit quality, whereas time budget pressure diminish the caliber of audit quality.